Continuous Visual Survey on Highway Br-010: Case Study on the Stretch between Estreito and Porto Franco – Ma. - Brito, Francyléia R.; Santos, Rafaella O. G. (International Journal of Advanced Engineering Research and Science, 2021)
Over the past decades, Brazil has exhibited economic growth in several sectors. This growth raises important questions about the quality and performance that Brazilian transportation offers the population. The road modal is the most used for transportation of cargo and people in the country. Due to the great demand of this modal, the quality of the highways is affected and end up presenting defects in the sidewalk, signaling, geometry, among others. In this context, the study aimed to evaluate the surface quality of the sidewalk of BR 010, in the stretch between the cities of Estreito - MA and Porto Franco - MA. The study was based on the application of the Continuous Visual Surveys (CVS) methodology, presented in the DNIT Procedure PRO 008/2003, which aims at identifying and quantifying the defects present on the sidewalk surface. Through the results obtained it was possible to identify that the most pertinent pathology throughout the stretch was isolated cracks found in 85.2% of the segments. On the other hand, the least present pathology was slipping, found in only 40.70% of the analyzed segments. Based on the calculations of the Surface Condition Index (SSI), it was possible to classify the stretch according to the quality of the sidewalk surface. 37% of the stretch is in good condition, 51.90% is considered regular, 7.40% is bad and 3.70% is considered to be in very bad condition. From the results obtained in the evaluation it is possible to have a basis to assist in decision making for interventions or reconstruction of critical stretches.